The influence of a multistage mountain-bike race on neuromuscular activation and synergies: A case study. - Eken, M. M.; Arnold, S. L.; Thijssen, J.; van der Schaaf, M.; Engelbrecht, L.; Lamberts, R. P. (International Journal of Sports Physiology and Performance, 2023)
Introduction This case study aimed to describe potential changes in neuromuscular activation and synergies after an 8-day cross-country mountain-bike stage race.